YOUTHS’ KNOWLEDGE AND PRACTICES OF THE PALM OIL INDUSTRY IN MALAYSIA - Maros, Marlyna; Rahman, Anis (PEOPLE: International Journal of Social Sciences, 2017)
Working in the palm oil industry can be challenging, especially those involved in the plantation field. The Malaysians’ general perception about palm oil industry revolves around the lower tier of the occupation that contributes to the first impression whenever working at palm oil industry is mentioned. The job includes planters, cultivators, machine operators and site managers. This however is just the tip of the iceberg in the industry. The most publicized due to the workforce issue in this industry would be foreign workers and the settlement of the plantation itself. There are concerns over crimes and social issues arising from this condition. The researcher believes that one way to solve this concern is to derive human resources from the youths of the country. Youths should be exposed to the job opportunities in oil palm industry and efforts should be made to improve on the perceptions of the work related to this industry. This can be done by increasing the youths’ knowledge and appreciation on the palm oil industry in Malaysia. This could just be a presumption as there is no reference of the levels of awareness among Malaysian youths regarding the palm oil industry. Hence, this research aims to investigate the Malaysian youths’ knowledge, attitude and application of the palm oil industry. To achieve this objective, a Needs Analysis was carried out from a set of questionnaire designed based on the KAP (Knowledge, Attitude, and Practice) framework and administered to 281 multiracial youths from rural and urban areas around the country. Discussions in this paper will be based on the Needs Analysis of the knowledge and practice among the youths in oil palm and palm oil industry. The paper ends with suggestions on how to stimulate interest among Malaysian youths in this industry.